2018
DOI: 10.1007/s10646-017-1891-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glyphosate formulations on the population dynamics of two freshwater cladoceran species

Abstract: The general objective of this work is to experimentally assess the effects of acute glyphosate pollution on two freshwater cladoceran species (Daphnia magna and Ceriodaphnia dubia) and to use this information to predict the population dynamics and the potential for recovery of exposed organisms. Five to six concentrations of four formulations of glyphosate (4-Gly) (Eskoba, Panzer Gold, Roundup Ultramax and Sulfosato Touchdown) were evaluated in both cladoceran species through acute tests and 15-day recovery te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
0
9
1
1
Order By: Relevance
“…For the last decade, the uses of herbicides have tremendously increased in vegetation control, agriculture and non-agricultural areas due to development of resistant of different crop varieties against glyphosate. Moreover, this herbicide is extensively used via aerial applications to remove unwanted weeds (Tarazona et al, 2017;Reno et al, 2018). The frequent and extensive applications of glyphosate in agriculture and public health have raised debate about its controversy toxicity (Blaylock, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the last decade, the uses of herbicides have tremendously increased in vegetation control, agriculture and non-agricultural areas due to development of resistant of different crop varieties against glyphosate. Moreover, this herbicide is extensively used via aerial applications to remove unwanted weeds (Tarazona et al, 2017;Reno et al, 2018). The frequent and extensive applications of glyphosate in agriculture and public health have raised debate about its controversy toxicity (Blaylock, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that a small quantity of pesticides reaches to the target pests and the huge part is spread in the environment. Reports are also available about the presence of glyphosate in surface water as a result of spraying over crops, rivers, streams, water flow and volatilization (Lopes et al, 2018;Reno et al, 2018). Earlier studies have shown that in glyphosate formulations some ingredients are highly toxic to non target species than glyphosate (Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The culture was maintained under constant conditions: continuous aeration, agitation (100 rpm), light intensity (8000 lux), temperature 24 ± 1°C, pH (6.5), and conductivity of the medium (1.4 mS/cm). Subsequently, the suspension was centrifuged (500 rpm for 7 min) to eliminate the saline medium and resuspended in culture of D. magna to obtain a working stock concentration with a density of algae of 1.02 × 10 6 cells/ml measured directly in a Neubauer chamber and indirectly, by spectrophotometry (absorbance = 1.5, λ = 650 nm) (Regaldo, Reno, et al, 2014; Reno et al, 2014, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Cladocerans represent an ideal group for the evaluation of toxicity at global level, due to their wide geographical distribution, ease of culture, high sensitivity to different xenobiotics, parthenogenetic reproduction and short life cycle. Among them, Daphnia magna is frequently used to study chemical substances in ecotoxicological tests (Regaldo, Gagneten, & Troiani, 2014; Reno et al, 2014, 2016, 2018; Silva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…O glifosato N-(fosfometil)glicina é um dos herbicidas mais utilizados na atualidade devido à elevada eficiência e relativa baixa toxicidade aos mamíferos, com uso intenso tanto na agricultura como em áreas urbanas (Duke e Powles 2008;Hanke et al 2010;Santadino et al 2014;Benbrook 2016;Reno et al 2018). É um herbicida sistêmico, não seletivo, pós-emergente e de amplo espectro de ação, atuando primariamente na inibição da enzima 5-enolpiruvishiquimato-3-fosfato-sintase (EPSP sintase) nas plantas.…”
Section: Introductionunclassified